2005
DOI: 10.1590/s0100-41582005000300017
|View full text |Cite
|
Sign up to set email alerts
|

Protection between strains of Passion fruit woodiness virus in sunnhemp

Abstract: The main objective of the present study was to evaluate the effect of the sunhemp (Crotalaria juncea) host species on the protective ability of two mild strains of Passion fruit woodiness virus (PWV), named F-101 and F-144, which had failed to protect passion flowers (Passiflora edulis f. flavicarpa) in previous experiments. The nucleotide sequences of the capsid protein (CP) gene and the 3'-non-translated region (3'-NTR) of these mild strains and the severe strain of PWV-SP were compared to confirm their rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As a result, in regions where the mild strains were irregularly distributed or were found at low concentrations, there may be free sites for superinfection with the severe strain to occur; because the severe strain is more competitive, it later invades the plants systemically. This breakdown on protection, however, did not occur in studies with sunn hemp plants (Crotalaria juncea L.) infected with the same mild strains of PWV (Novaes & Rezende, 2005). In this case, after analyzing the concentrations of mild strains in the plant tissues, the authors suggested that protection effectiveness was apparently associated with a more uniform concentration and distribution of mild strains in the tissues of this plant species.…”
Section: Resultsmentioning
confidence: 90%
“…As a result, in regions where the mild strains were irregularly distributed or were found at low concentrations, there may be free sites for superinfection with the severe strain to occur; because the severe strain is more competitive, it later invades the plants systemically. This breakdown on protection, however, did not occur in studies with sunn hemp plants (Crotalaria juncea L.) infected with the same mild strains of PWV (Novaes & Rezende, 2005). In this case, after analyzing the concentrations of mild strains in the plant tissues, the authors suggested that protection effectiveness was apparently associated with a more uniform concentration and distribution of mild strains in the tissues of this plant species.…”
Section: Resultsmentioning
confidence: 90%
“…The following aphid species are reported CABMV vectors in Brazil: Aphis craccivora , A. fabae , A. gossypii , Myzus persicae , Toxoptera citricidus and Uroleucon ambrosiae (Garcêz et al, 2015; Inoue et al, 1995). Under experimental conditions, A. fabae and A. solanella showed 40% efficiency in transmitting CABMV, whereas U. sonchi did not transmit the virus (Garcêz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%